Structure of rare-earth chalcogenide glasses by neutron and x-ray diffraction. (28th April 2017) - Drewitt, James W E; Salmon, Philip S; Zeidler, Anita; Benmore, Chris J; Hannon, Alex C
Abstract: The method of neutron diffraction with isomorphic substitution was used to measure the structure of the rare-earth chalcogenide glasses ( R 2 X 3 ) 0.07 (Ga2 X 3 )0.33 (Ge X 2 )0.60 with R = L a or Ce and X = S or Se. X-ray diffraction was also used to measure the structure of the sulphide glass. The results are consistent with networks that are built from Ge X 4 and Ga X 4 tetrahedra, and give R –S and R –Se coordination numbers of 8.0(2) and 8.5(4), respectively. The minimum nearest-neighbour R – R distance associated with rare-earth clustering is discussed.